Evaluation of the Existing Food Safety Management System (FSMS) Implemented in Sudanese Sugar industries - AM Babeker; MA Ebrahiem; AR Ahmed; GA Mustafa (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2022)
The present study was conducted in all Sudanese Sugar industries; namely; (Kenana, White Nile, Assalaya, Sennar, Guneid and New Halfa) during production season at 2017. The study aimed to evaluate the existence of food safety Management System implemented by all Sudanese sugar industries with reference to the Food Safety Management System (FSMS) of the International Standard Organization (ISO 22000). The data were collected using ISO 22000 checklist and direct interviews. Likert Five-Point Scale was used in scoring the checklist statement and the arithmetic mean was obtained. The results of the study revealed that the general requirement of the Food Safety Management System was not applicable; score less than (1.8 points) whereas its documentation that supports food safety programs scored major deficiencies in five industries less than 3.4 points. Secondly, the requirement of management responsibility attained non-compliance in three industries. Thirdly, the Requirement of Resource Management in all Sudanese sugar industries had major deficiencies except one factory scored minor deficiency less than 4.2 points. Fourthly, Planning and realization of safe products requirement was non-compliance in three factories less than 2.6 points and not applicable in the rest factories. Finally, the requirement of validation, verification and improvement of food safety programs was not applicable in all Sudanese Sugar Industries where it recorded less than 1.8 points. Lack of top management commitment and involvement and lack of government support represent the main constraints and barriers to implementing food safety systems in Sudanese sugar companies. Sudanese sugar industries need to implement food safety systems like GMP (Good Manufacturing Practices) and HACCP (Hazard Analysis Critical Control Point System) that represent the minimum requirement to implement Food Safety Management System.